Mesosphere Ozone and the Lower Ionosphere Under Plasma Disturbance by Powerful High-Frequency Radio Emission - Nataliya V. Bakhmetieva (Atmosphere, 2020)
We present the results of experiments on the Earth’s lower ionosphere at mesospheric heights by creating artificial periodic irregularities (APIs) of the ionospheric plasma and simultaneous measurement of the atmospheric emission spectrum in the ozone line by ground-based microwave radiometry when the ionosphere was disturbed by powerful high-frequency radio emission from the midlatitude SURA heating facility (56.15 °N; 46.11°E). The diagnostics of the ionosphere was carried out on the basis of measuring amplitudes and phases of signals scattered by periodic irregularities in the altitude range of 50–130 km. For each heating session lasting 30 min, two ozone spectra were measured. These spectra were compared with the measured spectra the periods when heating was turned off. During the heating session of the ionosphere, a decrease in the intensity of the microwave radiation of the atmosphere in the ozone line was observed. The lower ionosphere was characterized by intense dynamics. Rapid variations in the amplitude of the scattered signal and the relaxation time of artificial periodic irregularities were observed. The velocity of a regular vertical movement in the D-region of the ionosphere constantly varied direction with average minute values up to 4–5 m/s. We assume the decrease in the ozone emission spectrum at the altitude of 60 km can be explained by an increase in the coefficient of electron attachment to oxygen molecules during heating sessions. The lower boundary of the region enriched with atomic oxygen was estimated from the height profile of the API relaxation time.